Integrated Management of Spot Blotch Disease of Wheat (Triticum aestivum L.) Caused by Bipolaris sorokiniana (Sacc.) Shoem - Kumar, Deepak; Singh, Ramji; Prasad, Durga; Tomar, Ajay (International Journal of Economic Plants, 2025)
Spot blotch caused by Bipolaris sorokiniana has a worldwide distribution, however, it is most hostile when temperatures and relative humidity are high and soil fertility is poor. The disease causes a substantial loss in yield, particularly in India’s North Eastern Plains Zone. Field investigations were carried out from December to April for two consecutive crop seasons, 2021–2022 and 2022–2023 for the evaluation of fungitoxicants, botanicals, bio-agents, and micronutrients against spot blotch of wheat (Triticum aestivum L.) under the field conditions. The wheat genotypes were inoculated with an aqueous solution of the pathogen Bipolaris sorokiniana, which contained approximately 105 conidia ml-1. Two inoculations were made: one at the booting phase and another fifteen days later. Seven micronutrients-calcium chloride, zinc sulphate+lime, ferrous sulphate+lime, boron, sulfur, molybdenum, and manganese sulphate+lime-four botanicals-leaf extracts of tulsi, neem, mentha, and garlic clove extract-four bioagents-Trichoderma harzianum SV-7, T. harzianum SV-28, T. harzianum IRRI-1, Pseudomonas fluorescens-and six fungitoxicants-azoxystrobin, difenoconazole, propiconazole, tebuconazole, azoxystrobin+tebuconazole, and carbendazim+mancozeb-were assessed against spot blotch of wheat in artificially inoculated field conditions. Furthermore, 32 wheat genotypes were evaluated for resistance to spot blotch in addition to the above experiments. During two consecutive crop seasons, the study found that fungitoxicants (propiconazole and tebuconazole), botanicals (garlic clove extract), micronutrients (zinc sulphate and boron), and bioagents (Trichoderma harzianum-IRRI-1) were effective in decreasing the disease index and increasing grain yield.